Meningkatkan Keterampilan Berbicara Siswa SMA Dwijendra Gianyar Melalui Model Pembelajaran Contextual Teaching And Learning - Gatra, I Made (Journal of Education Action Reseach, 2018)
The purpose of this study was to improve students' speaking skills through the learning model Contextual Teaching and Learning (CTL) in class XI students in the odd semester of Dwijendra Gianyar High School in the academic year 2016/2017. Based on the results of classroom action research that has been carried out in two cycles with the use of the Contextual Teaching and Learning (CTL) learning model in Indonesian language learning, it can be concluded that there was an increase in speaking skills in class XI students of the Dwijendra Gianyar high school after learning with the use of models learning Contextual Teaching and Learning (CTL). This can be seen from the results of tests of students' speaking skills that are increasing in each cycle, namely the average value of observations in the first cycle 75.22 and increased to 83.85 in the second cycle. And seen from the results of the speaking skills test in the first cycle it was known that 14 of 27 students had reached the KKM score (75), and increased in the second cycle where 27 of 27 students had succeeded in achieving the KKM score (75). Based on the results of classroom action research using these two cycles, it turns out that the formulated hypothesis is proven to be true meaning it turns out the learning model steps Contextual Teaching and Learning (CTL) can improve speaking skills in class XI students in the odd semester of Dwijendra Gianyar High School 2016/2017.